P.101 Case-oriented needs assessment for professional development in an academic neurology centre. (2nd June 2017) - Choudhury, P; Cooke, L
Abstract : Background: Needs assessment is a cornerstone of designing programs for continuing professional development (CPD). However, typical needs assessment surveys often yield non-specific information insufficient to guide professional development programming decisions.Methods: A survey was distributed to Neurologists practicing in city of Calgary. A stimulated-recall method was used to generate specific case-oriented clinical questions and 5-point Likert scales were used to rate specific topics across the CanMEDS competency framework and CPD preferences.Results: A total of 48 surveys were distributed, with a response rate of 62.5%. Most respondents were subspecialists in Neurology (87%) in practice for less than 15 years (71%). Most used local neuroscience (97%) rounds as source for CPD. Respondents reported a need to address specific questions relating to the following topics: Acute stroke (54%), non-acute stroke (45%) and epilepsy (50%). For example, physicians identified that they wanted to learn more about when to reinitiate anticoagulation following ischemic stroke, or which choice of anti-epileptic for various seizure presentations. Specific medical content was rated highly disproportionately to other physician competencies such as communication or management skills.Conclusions: Our survey elicited detailed learning gaps from academic neurologists and identified a disconnect in interest in topics related to medical content compared to other important physician competencies.